Regeneration of Forest Resources Based on Tribal Enterprise: An Approach towards an Eco-Friendly Environment - Buddhadeb Chaudhuri; Chandreyee Roy (e-cadernos ces)
Due to deforestation, there is a growing trend in India, that the Government has started planting eucalyptus and other varieties of trees under the afforestaion programme for their commercial value. This has caused the disappearance of traditional forest trees and has triggered the change of the total eco-system of the forest in the eastern part of India. As leaf plates and bowls are made from the leaves of sal trees, the use of these plates and bowls can draw the attention of the Government towards the importance and economic value of the sal trees. This can definitely encourage the Government and the forest officials to plant more sal trees than eucalyptus trees, if the former are now regarded as “commercial plants”. Such practice can directly help indigenous people to sustain their livelihood, preserve the traditional craft and prevent the deforestation in this region as well.